PERAN KIAI DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL RELIGIUS DAN RESILIENSI SANTRI DI PONDOK PESANTREN NURUL HIKMAH SEBLAK JOMBANG - Ikhwana Azizah, Azzah Sayyidah; Ali Said (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The role of the kiai in developing santri’s religious emotional intelligence and resilience is a significant research context, considering that the kiai is a central figure in pesantren life with strong influence on santri’s character formation. Through role modeling, habituation of worship practices, guidance, and daily mentoring, the kiai directs santri’s to manage emotions in a healthy and religiously grounded manner while building mental resilience against the pressures of pesantren life. This study aims to: (1) describe the kiai’s role at Pondok Pesantren Nurul Hikmah Seblak Jombang; (2) analyze the kiai’s role in developing santri’s religious emotional intelligence and resilience; and (3) identify the supporting and inhibiting factors influencing that role. A qualitative approach with a case study design was employed, with data collected through observation, semi-structured interviews, documentation, and triangulation. Findings indicate that: first, the kiai performs multidimensional roles as educator, caregiver, role model, participative leader, and community unifier; second, the development of religious emotional intelligence and resilience is facilitated through muhasabah habituation, worship discipline, reinforcement of patience and tawakkal values, and sustained personal mentoring; third, the religiously conducive pesantren environment and kiai-administrator synergy are key enabling factors, while disparate student backgrounds, digital technology influences, and limited personal mentoring time constitute the main inhibiting factors. The kiai’s role is thus affirmed as a determining factor in shaping santri’s who are emotionally mature, mentally resilient, and religiously principled.